2020
DOI: 10.1186/s13054-020-02962-y
|View full text |Cite
|
Sign up to set email alerts
|

How machine learning could be used in clinical practice during an epidemic

Abstract: The COVID-19 epidemic is the cause of a crisis that is confronting the healthcare community with an unprecedented situation: emergency and intensive care units (ICU) are saturated, compelling physicians to make extremely hard decisions (triage). In such a resourceconstrained situation, physicians need decision support systems that could help them to optimally stratify patient risk. In the present paper, we explain how machine learning (ML) could help clinical practitioners during the epidemic (Fig. 1), and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…Because these symptoms also occur in common colds, it is mandatory to know others that can occur, such as nasal congestion (rhinorrhea), diarrhea and rashes, or color changes in fingers or toes. Based on our information, the major symptoms among infected patients were: fever, headache, cough, and dyspnea (78.51%, 76.14%, 74.28%, and 38.54%), which have been consistent in several studies with the highest reported percentages [6] , [10] . We can point to dyspnea as the comorbidity that can distinguish more patients in a risk scenario because its prevalence percentage is 86.29% of cases.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Because these symptoms also occur in common colds, it is mandatory to know others that can occur, such as nasal congestion (rhinorrhea), diarrhea and rashes, or color changes in fingers or toes. Based on our information, the major symptoms among infected patients were: fever, headache, cough, and dyspnea (78.51%, 76.14%, 74.28%, and 38.54%), which have been consistent in several studies with the highest reported percentages [6] , [10] . We can point to dyspnea as the comorbidity that can distinguish more patients in a risk scenario because its prevalence percentage is 86.29% of cases.…”
Section: Methodssupporting
confidence: 86%
“…Indeed, one aspect that we can highlight from the various studies on the COVID-19 pandemic is that it has driven unprecedented technological developments. Many of these relate to Artificial Intelligence and Machine Learning, and their interaction with diverse areas of knowledge, whether medical, social or economic; including the sciences of massive data and computational analysis [10] , [13] . Amidst this scenario, the health sector will need to incorporate these resources into its analysis and diagnosis support systems, not only of infectious diseases but of any other nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected patients experience symptoms such as fever, fatigue, dry cough, and dyspnea [ 8 ]. Some researchers have attempted to detect these symptoms using non-contact devices and machine learning algorithms [ 9 ]. They focused on two main issues: the features extracted from the subject and the algorithms used to recognize infected subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, machine learning (ML) has been studied in clinical research to support decision-making [13,14]. However, how machine learning is used in general practice remains a challenge [15].…”
Section: Introductionmentioning
confidence: 99%